Non‐alcoholic fatty liver disease fibrosis score and FIB‐4 scoring system could identify patients at risk of systemic complications. Issue 6 (15th October 2014) - Takahashi, Yuka; Kurosaki, Masayuki; Tamaki, Nobuharu; Yasui, Yutaka; Hosokawa, Takanori; Tsuchiya, Kaoru; Nakanishi, Hiroyuki; Itakura, Jun; Izumi, Namiki
<x xml:space="preserve">Abstract</x> Aim To investigate the relation between systemic complications of non‐alcoholic fatty liver disease (NAFLD) and non‐invasive fibrosis scores. Methods The NAFLD fibrosis score (NFS) and FIB‐4 were measured in 1559 people who underwent a complete medical checkup at our hospital and were followed for more than 3 years. Correlation between these scores and prevalence and new incidence rates of diabetes or cerebral–cardiovascular diseases were analyzed. Results The 1559 cases were classified into two groups using the low cut‐off values of NFS and FIB‐4: group 1 (≥low cut‐off score with fatty liver) and group 2 (the others). In group 1, the prevalence of diabetes and cerebral–cardiovascular diseases at baseline and additional incidences during the observation period was higher compared with group 2. Diabetes at baseline in group 1 versus group 2 were 31.5% versus 3.1% (NFS, P < 0.0001), 17.0% versus 4.7% (FIB‐4, P < 0.0001), and cerebral–cardiovascular diseases at baseline were 7.7% versus 2.3% (NFS, P = 0.002) and 9.0% versus 2.3% (FIB‐4, P = 0.0012). New incidences of diabetes were 4.5% versus 1.2% (NFS, P = 0.034) and 3.6% versus 1.2% (FIB‐4, P = 0.11), and of cerebral–cardiovascular diseases were 5.0% versus 0.9% (NFS, P = 0.0019) and 5.4% versus 0.9% (FIB‐4, P = 0.0034). Conclusion NFS and FIB‐4 are useful to extract cases with high risk of systemic complications of NAFLD in the public.